Discontinuation of Everolimus Due to Related and Unrelated Adverse Events in Cancer Patients: A Meta-Analysis. (14th September 2017) - Rogers, Sherise C.; Garcia, Christine A.; Wu, Shenhong
ABSTRACT: A meta-analysis of randomized controlled trials (RCTs) was performed to examine the risk of everolimus discontinuation due to related and unrelated adverse events (AE) in cancer patients. Fifteen RCTs were analyzed that compared everolimus to placebo and reported discontinuation due to AE with everolimus (related and unrelated to everolimus) and placebo (unrelated to everolimus). Incidence of discontinuation with everolimus due to AE and placebo was 12.3% and 4.7% respectively. Relative risk of everolimus discontinuation due to related AE was 2.60. Risk of discontinuation varied by tumor type, however everolimus dose or concomitant chemotherapy was not significant.